Electrochemical radical cation aza-Wacker cyclizations - Adachi, Sota; Okada, Yohei (Beilstein Journal of Organic Chemistry, 2024)
Electrochemical or photochemical single-electron oxidation of bench-stable substrates can generate radical cations that offer unique reactivities as intermediates in various bond-formation processes. Such intermediates can potentially take part in both radical and ionic bond formation; however, the mechanisms involved are complicated and not fully understood. Herein, we report electrochemical radical cation aza-Wacker cyclizations under acidic conditions, which are expected to proceed via radical cations generated by single-electron oxidation of alkenes.
Keywords: alkene; aza-Wacker cyclization; electrochemistry; radical cation; sulfonamide